2021
DOI: 10.3389/fcvm.2021.682357
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs as Competing Endogenous RNAs in Cardiovascular and Cerebrovascular Diseases: Molecular Mechanisms and Clinical Implications

Abstract: Circular RNAs (circRNAs) represent a novel class of widespread and diverse endogenous RNA molecules. This unusual class of RNA species is generated by a back-splicing event of exons or introns, resulting in a covalently closed circRNA molecule. Accumulating evidence indicates that circRNA plays an important role in the biological functions of a network of competing endogenous RNA (ceRNA). CircRNAs can competitively bind to miRNAs and abolish the suppressive effect of miRNAs on target RNAs, thus regulating gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 74 publications
(108 reference statements)
0
15
0
Order By: Relevance
“…In terms of mechanism, it has been confirmed that circRNAs, as the competitive endogenous RNAs (ceR-NAs) of miRNAs, relieved the restriction of miRNAs on the expression of target genes, and thereby affected the cell biological functions [19]. This study confirmed that miR-488-3p was a candidate miRNA for circ-NT5C2 through bioinformatics analysis and related cell experiments.…”
Section: Introductionmentioning
confidence: 54%
“…In terms of mechanism, it has been confirmed that circRNAs, as the competitive endogenous RNAs (ceR-NAs) of miRNAs, relieved the restriction of miRNAs on the expression of target genes, and thereby affected the cell biological functions [19]. This study confirmed that miR-488-3p was a candidate miRNA for circ-NT5C2 through bioinformatics analysis and related cell experiments.…”
Section: Introductionmentioning
confidence: 54%
“…As competing endogenous RNA (ceRNA) circRNAs compete with messenger RNAs (mRNAs) for microRNAs (miRNAs). By sharing common miRNA response elements (MREs), circRNAs can act as miRNA “sponges” to regulate mRNA activity targeted by normal miRNA [ 27 , 28 ]. To find a potential ceRNA network for circWDR37, we constructed the circWDR37-miRNA-mRNA network via bioinformatics.…”
Section: Resultsmentioning
confidence: 99%
“…CircRNAs have been linked to the development of a number of cardiac diseases, including atherosclerosis, myocardial damage, heart failure, and drug-induced cardiotoxicity, according to research (Min et al, 2021). The current emphasis of circ-ITCH research in cardiac diseases is ischaemia-reperfusion (I/ R) injury and doxorubicin-induced cardiotoxicity (DOXIC).…”
Section: Cardiac Diseasesmentioning
confidence: 99%